THE EFFECT OF INVESTMENT DECISIONS, PROFITABILITY AND DEBT POLICY ON STOCK PRICES IN START-UP COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019-2023 - Indah Sari Yusmita; Rico Nur Ilham; Ghazali Syamni; Muttaqien (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This research examines the effect of Investment Decisions (PER), Profitability (ROE) and Debt Policy (DER) on Stock Prices in start-up companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Research data can be accessed on the official website www.idx.co.id. The thesis preparation technique uses purposive sampling so that the sample in this study is 8 companies and has 40 observation data. The data analysis tool in this study uses the Panel Data Regression method with the Eviews 12 application tool with the Random Effect Model. The results of the study found that Investment Decisions (PER) have a positive and significant effect on stock prices. Profitability (ROE) has a positive and significant effect on stock prices. Debt policy (DER) has a negative but not significant effect on stock prices. Simultaneously, Investment Decision (PER), Profitability (ROE) and Debt Policy (DER) have a positive and significant effect on stock prices.